Estudo in vivo do potencial anti-inflamatório do Otosporin empregado em dentes de rato submetidos à clareação dentária - Álamo, Larissa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Otosporin, drug indicated for the treatment of otitis externa, is also employed in various endodontic procedures such as capping, pulpotomy and as a root canal dressing in cases of biopulpectomia. Although widely studied by medical and dental field has not yet been explored as dental post-bleaching agent. It is known that the hydrogen peroxide (H2O2) of bleaching gel can cause biological effects to pulp tissue, that vary from inflammation to necrosis. The objective of this study is to assess the anti-inflammatory potential of Otosporin in teeth submitted to dental bleaching. 20 rats were divided into 4 groups of 10 hemi-maxilla each. Was held the aplication of agent bleaching in molars of the right hemi-maxilla, for 30 minutes of application. The molars of the left hemi-maxilla received the bleaching agent vehicle and served as control. . Half of the animals received application of Otosporin for 10 minutes in each molars. Other half received vehicle Otosporin, composed the following groups: G1A- bleaching agent followed by Otosporin; G1B- vehicle bleaching agent followed by Otosporin; G2A- bleaching agent followed the vehicle Otosporin; G2B- vehicle bleaching agent followed the vehicle Otosporin. After 2 days, the animals were euthanized and the jaws removed and processed for evaluation in optical microscopy. Tissue sections were stained with HE and evaluated by pre-established criteria by assigning scores to microscopic events. The results were analyzed statistically by the Kruskal Wallis and Dunn tests (p <0.05). It was observed in cleared specimens where the Otosporin was used, the presence of mild inflammatory infiltrate, with a significant difference with the cleared that no received application of Otosporin and showed severe inflammatory infiltrate to necrosis in the coronal pulp. We conclude that the Otosporin when applied topically...

O Otosporin, medicamento indicado para o tratamento de otite externa, é também empregado em diversos procedimentos endodônticos tais como, capeamento, pulpotomia e como curativo de demora em casos de biopulpectomia. Apesar de amplamente estudado pela área médica e odontológica, ainda não foi explorado como agente anti-inflamatório pós-clareação dentária. Sabe-se que o peróxido de hidrogênio (H2O2) contido no gel clareador pode causar danos à polpa dentária, que variam de inflamação à necrose pulpar. Assim, o objetivo deste estudo foi verificar o potencial anti-inflamatório do Otosporin em dentes submetidos à clareação dentária. Foram utilizados 20 ratos divididos em 4 grupos, contendo 10 hemi-maxilas cada. Os molares superiores direito de cada animal receberam o agente clareador, enquanto que os molares superiores esquerdo receberam o veículo do agente clareador. Metade dos animais recebeu a aplicação do Otosporin por 10 minutos sobre cada molar, e a outra metade, o veículo do Otosporin, formando os seguintes grupos: G1A- agente clareador seguido do Otosporin; G1B- veículo do agente clareador seguido do Otosporin; G2A- agente clareador seguido do veículo do Otosporin; G2B - veículo do agente clareador seguido do veículo do Otosporin. Após 2 dias, os animais foram eutanasiados e as maxilas processadas para avaliação em microscopia óptica. Os cortes teciduais foram corados em H.E., foram avaliados atribuindo-se escores ao critério infiltrado inflamatório. Os resultados foram submetidos à análise estatística, pelos testes de Kruskall Wallis e Dunn (p < 0,05). Os espécimes clareados que receberam a aplicação do Otosporin apresentaram infiltrado inflamatório leve no tecido pulpar na região de cornos pulpares, com diferença significativa em relação aos clareados que não receberam a aplicação...
Keywords: Clareamento dental; Pulpite; Agentes anti-inflamatórios; Teeth bleaching